Genetic and physical analyses of Methylobacterium organophilum XX genes encoding methanol oxidation. - Machlin, S M (1988)
When allyl alcohol was used as a suicide substrate, spontaneous mutants and UV light- and nitrous acid-generated mutants of Methylobacterium organophilum XX were selected which grew on methylamine but not on methanol. There was no detectable methanol dehydrogenase (MDH) activity in crude extracts of these mutants, yet Western blots revealed that some mutants still produced MDH protein. Complementation of 50 mutants by a cosmid gene bank of M. organophilum XX demonstrated that three major regions of the genome, each of which was separated by a minimum of 40 kilobases, were required for expression of active MDH. By subcloning and Tn5 insertion mutagenesis of subcloned fragments, at least 11 genes clustered within these three regions were subsequently identified. The identity of the MDH structural gene, which was initially determined by hybridization to the structural gene of Methylobacterium sp. strain AM1, was confirmed by Western blot analysis of an MDH-beta-galactosidase fusion protein.